APPLICATION OF 3D MODELLING TECHNIQUE FOR ERGONOMIC IMPROVEMENT OF MANUFACTURING ASSEMBLY LINE WORKSTATION - MUYIWA, Omotunde; Oriolowo, Kolawole Taofik; Olaleye, Emmanuel Oluwaseun (Journal of Engineering and Technology (JET), 2026)
An ergonomically workstation design is vital for improving workers’ health, safety, and productivity in manufacturing industries where workers are not guided against repetitive tasks, awkward postures, and restricted workspaces. Studies have shown that these conditions often contribute to musculoskeletal disorders, fatigue, and absenteeism, which impact both employee and organization. This study was designed to apply 3D modelling and digital human simulation techniques to evaluate and redesign an assembly line workstation in Nigeria using anthropometric data of the participants. Fifty experienced workers were purposively selected, and data were collected using structured questionnaires and direct observation. Ergonomic risks were evaluated using the Rapid Upper Limb Assessment (RULA), while Autodesk Fusion 360 and Jack Siemens 8.4 software were used for modelling, simulation, and validation of the redesigned workstation. Findings revealed that 90% participants reported discomfort, mainly back pain (40%) and wrist pain (18%), while 86% reported poor tool accessibility and gave RULA score between 6 and 7. The redesigned workstation improved postures, reduced bending and awkward reaches, and achieved a RULA score of 2, indicating low ergonomic risk. Therefore, integrating modelling and simulation-based ergonomic intervention in workstation design provides a proactive and cost-saving solution for improving workers’ well-being and increasing productivity.